Réponses

Meilleure réponse !
  • Utilisateur Brainly
2013-05-22T21:05:08+02:00

a) A=(2x-3)(x+4)+(x+4)²

       =2x²-3x+8x-12+x²+8x+16

       =3x²+13x+4

 

b) A=(2x-3)(x+4)+(x+4)²

       =(x+4)(2x-3+x+4)

       =(x+4)(3x+1)

 

c) si x=√3 alors A=3*(√3)²+13√3+4=13+13√3

    si x=1-√2 alors A=3*(1-√2)²+13(1-√2)+4

                                  =3(1-2√2+2)+13-13√2+4

                                  =9-6√2+17-13√2

                                  =26-19√2

 

d) A= donne (x+4)(3x+1)=0

donc x+4=0 ou 3x+1=0

donc x=-4 ou x=-1/3

sur ID on obtient S={-4}